Pemanfaatan Geopolimer Dari Kaolin Sebagai Adsorben Untuk Mengolah Air Gambut - Imelda Dewi Agusti; Edy Saputra; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Basicly peat water is belong to surface water which is found in the wet land, like Riau Province. The characteristic of peat water are high color intensites (yellow or brown red), high organic content and low pH values about 2-5. For use as water source for domestic purposes, it was a process to change peat water toward clean water. One of the process was adsorption way. In this research is required by kaolin based geopolymers as adsorbent.The variable that used in this research is the mass of the adsorbent (1; 1,5; 2; and 2,5 gram, and stirring (time between 30,60 and 90 seconds) then tested of organic content. The best result from this research is that the adsorbent mass of 1 gram and the stirring time of 30s while adsorbent can increase from 51,192 mg/l to 0,63 mg/l on organics content. The results of this research indicated that the peat water treatment in accordance with the Decree of the Minister of the Health No. 416 Year 1990 and could be use kaolin based geopolymer as an alternative to peat water treatment .Keyword : Kaolin, Geopolymer, Adsorption, Peat Water